2011
DOI: 10.2480/agrmet.67.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of paddy rice heading date under projected climate change conditions for Hokkaido region based on the field experiment

Abstract: Impact assessment and adaptation planning to enable growth of paddy rice (Oryza sativa L.) under conditions of ongoing climate change are necessary in the Hokkaido region of northern Japan because of the intensive climate warming ( 2-3 in summer) projected to occur during the 21st century. Most previous studies have been based on extrapolation of results from past and present experimental data on unexperienced warming conditions under projected climatic change. These facts motivated us to use an assessment met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…6). This result is consistent with the results of open-field experiments designed to assess the effects of warmer conditions than present (Nemoto et al 2011a).…”
Section: Cultivation Possibility For Future Climatesupporting
confidence: 92%
See 3 more Smart Citations
“…6). This result is consistent with the results of open-field experiments designed to assess the effects of warmer conditions than present (Nemoto et al 2011a).…”
Section: Cultivation Possibility For Future Climatesupporting
confidence: 92%
“…Our results indicated that heat risks not currently existing will occur in Hokkaido under the highest projections of climatic warming (14.78C). In fact, rice yield in Hokkaido decreased in 2010 owing to abnormally high temperatures (12.28C), especially from the end of June to early July, which shortened the vegetative growth period and reduced the number of tillers and number of grains per plant (Nemoto et al 2011b). This was the first time a reduction in rice yield caused by hot conditions had been recorded in Hokkaido.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, introducing the 'southern cultivars' would be an effective way to adapt to the future climate in approximately 36% of the study area. An observational study also suggested the introduction of a southern cultivar to mitigate the hightemperature damage projected for the current leading cultivars (Nemoto et al 2011).…”
Section: Discussionmentioning
confidence: 99%